Membentuk Peserta Didik Jauh dari Konflik dan Fanatisme Sempit - Hesty Sinaga; Selfius Dur; Rainaldi Setiawan; Hisardo Sitorus (Pusat riset dan Inovasi Nasional, 2025)
The diversity of Indonesian society, which consists of various ethnic groups, religions, cultures, and races, represents a great potential for the creation of a harmonious social life. However, the reality shows that intolerance and narrow fanaticism still often arise and even begin to influence students in the educational environment. This has the potential to create social conflicts and damage the nation's character in the future. This study aims to examine the role of education in shaping students to avoid fanatic behavior and social conflicts. The research method used is descriptive qualitative with data collection techniques through relevant literature studies. The results of the study show that schools have a strategic role in instilling values of tolerance, inclusive attitudes, and religious moderation through learning, teacher role models, and a school culture that respects diversity. In addition, synergy between schools, families, and communities is needed to create an educational environment that is conducive to the development of students' character. Through the implementation of multicultural education and the strengthening of national values on a sustainable basis, students are expected to become a generation with strong character, tolerant, and able to live peacefully alongside others in a pluralistic society.